Strengthening The Relationality of Heteronomous and Autonomous Legal Rules in Workers’ Decent Wage Law Policies (An Attempt to Create a Dignified Tripatrid Ecosystem) - Hamzah, Any Suryani (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
The Job Creation Act (Ciptaker) protects the interests of employers (corporations) by omitting the heterogeneous Legal terms that are integrated (coherent) into the State and the workers expect to provide protection for workers in the context of determining and providing decent wages for workers. These legal circumstances demonstrate that, under the Job Creation Act, the application of autonomous legal norms predominates over the application of heteronomous legal principles. Such a situation affects the obscure presence of the State in providing decent employment for workers and upsets the tripartite ecosystem. It is employed to restore the degradation of the quality of the relationship between the two parties within the Job Creation Act. Therefore, it is necessary to make legal reconstruction efforts related to matters associated with the determination and payment of wages for workers in the Job Creation Act that emerge uncertainty and injustice for workers, to produce a formulation of a decent and fair wage legal policy to establish a relationship between the state, workers, and decent employers (Tripart ides). This research uses normative legal research methods, the type of research used in juridical normative research is descriptive. As for the approaches used in this research, there are several methods found in normative law research, among others: conceptual approaches, and philosophical approaches.